Paradigma Tabligh Dalam Dakwah - Muhammad Abdurrauf Nasrullah; Khusnul Khotimah (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Da'wah is the process of communicating divine messages to others. In order for the message to be understood properly, it is necessary to master effective and efficient communication. Without communication, the process of delivering messages will not take place properly, this communication is also called tabligh. This study was conducted to analyze how da’wah carried out within the limits of the tabligh paradigm. This research uses a qualitative-descriptive approach through literature study. The results of this study show that in da’wah activities, there is a complementary nature with each other. The existence of tabligh or communication activities allows the implementation of da’wah activities, as well as da’wah means the carrying out of the duties of a tabligh. This paradigm becomes a benchmark point for da’wah communication actors, which affects the technical material, and communication ethics. When tabligh performs the function of da’wah, the role of tablighi becomes noble. This is where tabligh or communication functions as a communicator of da'wah in carrying out its role.”